Avoiding the Practice of Social Discrimination by Using Speech Acts in The Novel Wuthering Heights by Emily Bronte - Ayu Diah Rahmah Sari; Wahyuni (Prologue: Journal on Language and Literature, 2023)
There are two objectives of this research; 1) to find out the types of speech acts  and 2) to describe the speech acts used to avoid the practice of social discrimination. As for the data, they were collected from the quotation from the novel. The result of this research is concluded that illocutionary acts as much as 57% or equal to 51 out of 90 data dominated to avoid the practice of social discrimination in the form of verbal expression (37%), avoidance (15%), exclusion (4%), and physical abuse (18%). After that, followed by locutionary acts as much as 34% or equal to 31 out of 90 data is also used to avoid the practice of social discrimination in the form of verbal expression (11), avoidance (4%), physical abuse (18%), and it does not appear at all to avoid exclusion. Lastly, perlocutionary acts as much as 9% or equal to 8 out of 90 data, it less appear to avoid the practice of social discrimination in the form of avoidance (4%), exclusion (2%), and it does not appear at all to avoid verbal expression, and physical abuse.